If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.6(y + 3) = 48 Reorder the terms: 0.6(3 + y) = 48 (3 * 0.6 + y * 0.6) = 48 (1.8 + 0.6y) = 48 Solving 1.8 + 0.6y = 48 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-1.8' to each side of the equation. 1.8 + -1.8 + 0.6y = 48 + -1.8 Combine like terms: 1.8 + -1.8 = 0.0 0.0 + 0.6y = 48 + -1.8 0.6y = 48 + -1.8 Combine like terms: 48 + -1.8 = 46.2 0.6y = 46.2 Divide each side by '0.6'. y = 77 Simplifying y = 77
| A=2lw+2lh+2wh | | 2x^2-2xy+y^2-4x+2y+1=0 | | 3x-5=13x-5 | | 7x-2=3x+8 | | 7(3x-5)=5(3x-8) | | 7x+3=158 | | 2x-3=6x+4x | | -32y^2-24y=0 | | ax=bx-3y+5 | | (6x-2)=3(x+1)+6 | | .25y+6=.2y | | 7x-(2x+4)=1 | | 5w^2-5W=0 | | 4+7(x-1)=7-2(x-2) | | b^2+6b=0 | | 6x+3=-(x-31) | | a(x)+b=c(x)+d | | ax+b=cx+d | | -8x+76+12x=4(3x-5) | | 10x^2-360= | | -2(3n+3)=8 | | 2(8-x)=3(-9+2x)+6 | | 11y-7=53-y | | 8b^2-10b=3 | | 2(f+3)+-2=8+2f | | 3x-4+x+1+2x+1=180 | | x^2-6x+15=6 | | 9c-3=24 | | 0.6(10000)+0.8x=0.72(10000+x) | | 0.6(10000)+0.8x=9.72(10000+x) | | 2n+6=0 | | 3a-6=a+4 |